New Discourses of Masculinity in the Context of Online Misogyny in Spain: The Use of the “Feminazi” And “Gender Ideology” Concepts on Twitter - Núñez Puente, Sonia (2021)
One of the effects of the advance of feminism in Spain in recent years has been the production of a discursive array of new masculinities. Some of the clearly misogynistic masculinities are linked to a discursive use of the term “feminazi”, which, together with the broader concept of “gender ideology”, contributes to the articulation of a specific narrative of masculinity. We propose a critical analysis of a sample of tweets with these two hashtags collected between 3 and 9 March 2019, coinciding with the #8M strike. We have established three dimensions of analysis for the qualitative study of these tweets: the war on the normal bloke, the mirror discourse, and feminist tyranny. The operationalization of these categories has allowed us to reveal the discursive processes through which the co-optation of the victim’s space by popular misogyny operates. Similarly, our analysis shows the crucial role that mass media plays in consolidating certain stories around hegemonic masculinity in the digital space.